SISTEM PERTANGGUNGJAWABAN PIDANA KORPORASI BAGI LEMBAGA PERBANKAN DALAM UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 10 TAHUN 1998 TENTANG PERUBAHAN ATAS UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 7 TAHUN 1992 TENTANG PERBANKAN - Kristian Kristian; Alvin Sebastian Kurnia (Jurnal Hukum Mimbar Justitia, 2018)
In order to make development in the field of economics to support and keep continuity of the implementation of national development that increase of the development and the result evenly, to raise of economic growth and to keep the stability of national development, to raise standard of living peoples (increase of prosperity of people), to create atmosphere of Indonesian that is fair and prosperous and create social fairness for all Indonesian, government need to form financial institution which is bank. Bank is seen as an institution that can obtain those goals because the bankâ€™s role as intermediation institution or act as financial intermediary as well as act as â€œagent of developmentâ€. The existence of bank as a corporate itself hold role more in the living of modern society.Â  However, the existence of bank its self should be wary because the bank not always gives the positive effect forever. In short, the existence of the bank can also give the negative effect, which is bank as a criminal and the bank can do the crime itself, including the following: telemarketing fraud, client fraud, grind and embezzlement customerâ€™s funds or debtor, various form of crime in the field of credit, make engineering report, make false record or make double accounting to save the reputation itself, abuse of authority, etc. the bank crime is one of form white collar crime, an organized crime that is systemic and extraordinary crimes, and new dimension of crime. This crime can occur because of the involvement of the business actors themselves, both from the bottom to the board of directors and even shareholders of the bank. As a law state, protection of people (in the framework of the welfare of the society) shall be done in every aspect. This protection shall be made against certain irresponsible acts, one of which is protection against the prevalence of "banking crime". In that context, considering the functional institution of bank is so important and prevalence of banking crimes that occur raises a question for authors, is it possible that corporate criminal liability systems are applied to banks? On that basis, this paper will discuss the implementation of corporate criminal liability system for banking institutions according to Indonesia law act number 10 of 1998 on Amendment to Act of the Republic of Indonesia Number 7 of 1992 concerning Banking. This research uses normative judicial research method by researching library materials.Â  On this basis, this paper will discuss the implementation of corporate criminal liability system for banking institutions according to the Law of the Republic of Indonesia act Number 10 of 1998 on Amendment to Law of the Republic of Indonesia Number 7 of 1992 Concerning Banking. This research uses normative juridical research method by researching library materials. The data used are secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The analysis method used in this study to conduct the method of content analysis (content analysis). The research result shows that the politics of law in the current banking law has not acknowledged the corporation (in this case is the bank) as the subject of the crime. The reason is because the system of criminal responsibility in the law is still charged to the caretaker (the man itself) as a subject of criminal. Thus, the current banking law still holds the principle of â€œsocietas delinquere non potestâ€ or principle of â€œuniversitas delinquere non potestâ€. To minimize the problems that related to the rampant banking crime and law enforcement in the banking sector, the current banking law needs to be reorientation, and reformulated by regulating corporations (banking institutions) and other corporations as subjects of crime. The results also show that the regulation of corporate criminal liability system for banking institutions gets legitimacy or justification philosophically, theoretically and sociologically. Therefore, it becomes a necessary and urgent need to revise immediately the Law of the Republic of Indonesia Number 10 of 1998 on Amendment to Act of the Republic of Indonesia Number 7 of 1992 concerning Banking (especially in regard to criminal provisions.Keywords: Criminal Liability, Corporate Crime, Bank, and Banking Act.